Contributions of Multivariate Statistics in Oil and Gas Industry - Freitas, Leandro Valim de; Freitas, Ana Paula Barbosa Rodrigues de; Marins, Fernando Augusto Silva; Veraszto, Estéfano Vizconde; Camargo, José Tarcísio Franco de; Davim, J. Paulo; Silva, Messias Borges (IntechOpen, 2013)
None